Analysis of Primary Surgery and Medical Treatment in the Management of Primary Open Angle Glaucoma - Abdul Majeed, Muhammad Akmal, M Afzal Khan Niazi, Ch. M. Tariq Munawwar Nadia Erum, Abdul Ghaffar (Journal of Rawalpindi Medical College, 2008)
Background: To evaluate and compare the efficacy of medical and surgical treatment for management of primary open angle glaucoma (POAG). Methods: Study included a total of 32 patients with 60 eyes, who were divided into two groups. 31 eyes were included in group A and were given medical treatment. 29 eyes were included in group B and were managed with primary surgery (Trabeculectomy). Results: The IOP was controlled in group A with one drug in 62.5% (n=10), with two drugs in 25% (n=4)and with three drugs in 6.25% (n=1). The IOP of group B patients was controlled by surgery alone in 81.25% (n=13) and with surgery and drugs in 18.75% (n=3). P values were found to be constantly less than 0.001. Conclusion: Primary surgery i.e. trabeculectomy is a superior modality of treatment for POAG as compared to medical therapy as it is cost-effective, IOP control is uniform and compliance is not a problem.